A interação grupal entre pares e sua repercussão no processo de construção da lecto-escrita - Isaia, Tatiane Peixoto (2008)
This research is inserted in the line of Currículo, Ensino e Práticas Escolares (Curriculun, Education and School Practices) from Programa de pós-Graduação em Educação da UFSM. The study had as objective to understand which the repercussion of group interaction partner in the construction of lecto-writing, investigating, therefore, the conceptual evolution about of understanding of lectowriting in children s literacy iitial process that shared conceptiones with your colleagues and of children s not that lived that same educational proposal. The studies of Ferreiro e Teberosky (1985), Piaget (1972; 1973; 1977a; 1977b; 1987; 1983; 1991; 2005), Vygotski (1984; 1988; 1993; 1998), Perret-Clermont (1996), among others, were used as theoretic contribution for the development of this investigation. The research was carried out at a institution of Education of the State of Rio Grande do Sul located at outskirts of Santa Maria. The subject participants were eight children s in literacy iitial process, being four children s each of the two classes of first grade of Ensino Fundamental chosen to be part of this study. The investigation was developed through a qualitative study, more specifically it was used from the perspective of case study ethnographic. The search of the findings was done through of the observations made in each class and registered in the inside the camp, semi structured interviews with the teachers of literacy of each class, questionnaire conducted with parents of the subjects of research and analysis of written spontaneous productions of the children. The findings the research showed that the impact of the actions of teachers of literacy of the classes A and B, themselves three types of group interaction partner, pointed in a the whole of three major categories: with a predominance of Cooperative Work (by Reciprocity; and, Conflicting), working with predominance of Traveller and with predominance of to Imitation. Each of these categories leaves emerge relevant factors to think teaching situations. So, it understood that the most significant conceptual advances in the elementary process of initial literacy happen when children have the opportunity to situations of living the group interaction partner in which prevladuje the cooperative work, both by reciprocity, as conflicting, since the understanding of how works the alphabetic system of the writing requires the sharing of chances and, mainly, the possibility of the subject to confront their conceptions with other subjects, through conflicts socio-cognitives encouraged by reflective work together.